Excess body mass is associated with T cell differentiation indicative of immune ageing in children. (9th April 2014) - Spielmann, G; Johnston, C A; O'Connor, D P; Foreyt, J P; Simpson, R J
Summary: Obesity has been associated with accelerated biological ageing and immunosenescence. As the prevalence of childhood obesity is increasing, we wanted to determine if associations between obesity and immunosenescence would manifest in children. We studied 123 Mexican American adolescents aged 10–14 (mean 12·3 ± 0·7) years, with body weights ranging from 30·1 to 115·2 kg (mean 52·5 ± 14·5 kg). Blood samples were obtained to determine proportions of naive, central memory (CM), effector memory (EM), senescent and early, intermediate and highly differentiated subsets of CD4 + and CD8 + T cells. Overweight and obese children had significantly lowered proportions of early CD8 + T cells (B = −11·55 and –5·51%, respectively) compared to healthy weight. Overweight children also had more EM (B = +7·53%), late (B = +8·90%) and senescent (B = +4·86%) CD8 + T cells than healthy weight children, while obese children had more intermediate CD8 + (B = +4·59%), EM CD8 + (B = +5·49%), late CD4 + (B = +2·01%) and senescent CD4 + (B = +0·98%) T cells compared to healthy weight children. These findings withstood adjustment for potentially confounding variables, including age, gender and latent cytomegalovirus and Epstein–Barr virus infections. We conclude that excess body mass, even in adolescence, may accelerate immunosenescence and predispose children to increased risks of incurring immune-related health problems in adulthood.